The first record of the tribe Cephenniini in South Africa, with new species of Cephennomicrus Reitter and Cephennodes Reitter (Coleoptera: Staphylinidae: Scydmaeninae) - Jałoszyński, Paweł (Zootaxa, 2013)
The tribe Cephenniini is recorded for the first time in the Republic of South Africa. Five new species are described and illustrated: Cephennodes (s. str.) lucipetus sp. n., C. (s. str.) zulunatalensis sp. n., C. (s. str.) mtubatubanus sp. n., C. (s. str.) sodwanaensis sp. n. (all from KwaZulu-Natal Prov.), Cephennomicrus ubomboensis sp. n. (KwaZulu-Natal), Cm. en-droedyi sp. n. and Cm. transkeianus sp. n. (from Eastern Cape). A distributional summary of continental Afrotropical Ce-phennodes and Cephennomicrus species is given, and taxonomic and evolutionary problems are indicated.